2019
DOI: 10.14238/pi59.3.2019.119-24
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophilic cationic protein level and hematological parameters in infants with cow's milk protein allergy

Abstract: Background Various biomarkers have been investigated in the diagnosis of cow's milk protein allergy (CMPA) in infants. To our knowledge, no prior studies have evaluated serum eosinophil cationic protein (sECP), neutrophil-lymphocyte ratio (NLR), and mean platelet volume (MPV) concurrently in infants with CMPA. Objective To compare sECP levels, MPV, and NLR in infants with and without CMPA, as well as to investigate the suitability of these parameters as biomarkers in the diagnosis of CMPA. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Vitamin D deficiency during childhood is known to cause growth retardation and nutritional rickets (2). Recently, an increasing number of studies have indicated that low levels of vitamin D may play an important role in the occurrence and development of extraskeletal diseases because of its immunoregulation and anti-inflammatory effects (3,4), such as allergic diseases (5), respiratory illnesses (6), and obesity in children (7). Although there is no consensus on the association between vitamin D and related health outcomes, most specialists believe that sufficient vitamin D is essential and protective for children's health.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency during childhood is known to cause growth retardation and nutritional rickets (2). Recently, an increasing number of studies have indicated that low levels of vitamin D may play an important role in the occurrence and development of extraskeletal diseases because of its immunoregulation and anti-inflammatory effects (3,4), such as allergic diseases (5), respiratory illnesses (6), and obesity in children (7). Although there is no consensus on the association between vitamin D and related health outcomes, most specialists believe that sufficient vitamin D is essential and protective for children's health.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the eosinophil count (495/mm 3 ) of the infants with a milk protein allergy was significantly lower at the first follow-up visit than before dietary intervention (655/mm 3 ) and that the number of eosinophils at the second follow-up visit (330/mm 3 ) was significantly lower than that at the first follow-up visit (495/mm 3 ). In a similar study by Dogan et al [ 43 ] found significantly higher eosinophil cationic protein levels (51.45 ng/mL) and blood eosinophil counts (475/mm 3 ) in infants with a milk protein allergy than in controls (17.55 ng/mL, 300/mm 3 ). Recently, Li et al [ 44 ] found that in 6-month-old infants with a milk protein allergy, eosinophil counts were higher than those of the nonallergic group (0.89 ± 0.45/mm 3 and 0.26 ± 0.12/mm 3 , respectively, p < 0.01).…”
Section: Discussionmentioning
confidence: 75%
“…All of the above studies have found that infants with a milk protein allergy have an increased number of eosinophils in their blood. The eosinophils formed in the bone marrow have large cytoplasmic granules, which contain eosinophil cationic protein, eosinophil protein X, and eosinophil-derived neurotoxin [ 43 ]. The eosinophil cationic protein encoded by the RNASE3 gene is a cytotoxic protein that enters the surrounding tissues when activated eosinophils degranulate and manifests as an increase in the level of eosinophils in the surrounding tissues [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation is needed into the characteristics and interactions among biochemical indicators of bone metabolism in children with CMPA to improve evaluation of bone metabolism status in children, reduce the incidence of metabolic bone disease, and more accurately monitor the effect of treatment. Many studies have shown that vitamin D is closely related to the occurrence and development of allergic diseases 7 ; however, the conclusions of these studies have not been consistent. Few studies have focused on the biochemical markers of bone metabolism in children with CMPA.…”
Section: Introductionmentioning
confidence: 93%